Wood-polymer composites utilizing degraded polyolefins as compatabilizers - Ndlovu, Sibusiso Sibongiseni (University of the Free State (QwaQwa Campus), 2011)
The effect of degraded LDPE (dLDPE) as compatibilizer on the morphology, as well as thermal, mechanical, and thermo-mechanical properties, of LDPE/wood flour (WF) composites was investigated in this study. The composites were prepared through melt mixing in a Brabender Plastograph internal mixer, while the LDPE was thermally degraded in an air oven at 80 oC for different periods of time. The formation of functional groups on the polyethylene chains during the degradation enables the dLDPE to be used as a compatibilizer. Composites with different amounts of WF, compatibilized with dLDPEs having different carbonyl indices, were characterized with scanning electron microscopy (SEM), Fouriertransform infrared (FTIR) spectroscopy, gel permeation chromatography (GPC), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA), as well as tensile, impact and hardness testing. Addition of dLDPE as compatibilizer generally enhanced the mechanical properties of the composites. The SEM images show smooth surfaces with fewer voids and fibre pullout for the dLDPE modified composites. The FTIR results show an increase in carbonyl index up to 7 weeks degradation, and the GPC results show that the molecular weight decreased significantly with increasing degradation time. The DSC results show that the presence of WF particles, and increasing filler loading, had very little influence on the melting and crystallization behaviour of the untreated LDPE/WF composites. However, in the dLDPE treated composites a nucleating effect of the fibres gave rise to increased LDPE melting and crystallization enthalpies. There was no significant improvement in the thermal stability of the dLDPE treated composites. The DMA results show that the presence of dLDPE (especially the 7 weeks dLDPE with a carbonyl index of 0.90) observably influenced the viscoelastic properties of the composites. In summary, it was found that the higher carbonyl index dLDPEs are more efficient compatibilizers in LDPE/WF composites, despite their significantly reduced molecular weights.
Dissertation (M.Sc. (Chemistry))--University of the Free State (Qwaqwa Campus), 2011
Keywords: Polymers; Polymers -- Mixing; Wood -- Chemistry; Composite materials